Genetic changes in the transforming growth factor beta (TGF-beta) type II receptor gene in human gastric cancer cells: correlation with sensitivity to growth inhibition by TGF-beta. - Park, K (1994)
We have found several genetic changes in the TGF-beta-type II receptor gene in human gastric cancer cell lines resistant to the growth inhibitory effect of TGF-beta. Southern blot analysis showed deletion of the type II receptor gene in two of eight cell lines and amplification in another two lines. The single cell line we studied that is sensitive to growth inhibition by TGF-beta showed no structural abnormalities of the type II receptor gene. Some of the gastric cancer cells resistant to the growth inhibitory effect of TGF-beta express either truncated or no detectable TGF-beta type II receptor mRNAs, whereas the one that retains responsiveness to the growth inhibitory effect of TGF-beta expresses a full-size type II receptor mRNA. Immunoprecipitation followed by Western blot analysis showed parallel changes in TGF-beta type II receptor expression. Our results suggest that one of the possible mechanisms of escape from autocrine or paracrine growth control by TGF-beta during carcinogenesis could involve genetic changes in the TGF-beta type II receptor gene itself or altered expression of its mRNA.